Phonetic Variability of Tatar Аnthropotoponyms in the Toponymy of the West Siberian Area - Khisamov, Oleg R.; Khalikov, Ilgiz I.; Khusainova, Alina Ya. (The New Research of Tuva, 2025)
The study examines the phonetic features of Tatar anthropotoponyms in the toponymy of the West Siberian area (Tyumen, Novosibirsk, and Kemerovo regions). The research aims to identify the specifics and regularities of phonetic variation in these names, determine the main types of sound changes, and analyze the factors influencing the emergence of their variants. During field expeditions to areas of compact Tatar settlement in the mentioned regions, 250 units of anthropotoponymic lexemes were collected. A comparative analysis was conducted between the collected terms and toponyms and their analogues in other dialects of the Tatar language, as well as in related Turkic languages. The analysis revealed a predominance of lexemes of Arabic-Persian origin (over 60%) and a significant proportion of Turkic etymons (over 20%). The share of borrowings from the Russian language amounted to a substantially smaller percentage (7%). The remaining 5% of anthropotoponyms require additional etymological examination. It was found that the most frequent phonetic processes are the devoicing of voiced consonants in initial and final positions, alternations of /ɕ/ and /t͡s/, /ʒ/ and /t͡ɕ/, /q/ and /k/, /x/, as well as the elision of sounds atypical for the native phonetic system, such as /h/ and /ʁ/. On the one hand, the phonetic structure of anthropotoponyms in the eastern dialect retains archaic features dating back to Old Turkic and demonstrates phenomena with a limited areal distribution within the Turkic language family, revealing similarities with the Altai-Khakass subgroup. On the other hand, it displays features characteristic of Kipchak languages.